Accelerating the Pace of Science: Improving Parenting Practices in Parents with Opioid Use Disorder. (3rd July 2019) - Cioffi, Camille C.; Leve, Leslie D.; Seeley, John R.
SYNOPSIS: A public health emergency exists in the United States as a result of rising overdose deaths related to Opioid Use Disorder (OUD). With the rise of OUD has also come an increase in the number of children exposed to parents who suffer from an OUD. There is a pressing need for parenting interventions for individuals with OUD to provide safe environments for the children being reared in the face of this epidemic. Research on parenting with an OUD is sparse, but it is impractical to move linearly from basic research to program development and implementation given the urgent need for intervention - a trajectory that prior research has established takes approximately 17 years. We have created an outline of strategies that can be used to accelerate the pace of science so that parenting practices are more immediately improved for this population. First, we summarize what is already known about OUD and parenting to characterize mechanisms that existing interventions have targeted and optimal settings for the wide dissemination of implementable interventions. Next, we identify existing interventions that either specifically target parents with OUD or mechanisms specific to parents with OUD. We describe four different approaches for accelerating the pace of science to improve the lives of parents with OUD and their children. By doing so, we hope to provide a roadmap for future researchers and practitioners to deliver more timely evidence-based interventions to address the additional burden placed on families and communities due to the rise in OUD in the United States.